Selection Indices in Linseed (Linum usitatissimum L.) suitable for rainfed condition - Ahmad, Ekhlaque; Ansari, Abdul Majid (Annals of Agricultural Research, 2016)
The discriminant-function technique was used to construct selection indices in 20 genotypes ofLinseed (Linum usitatissimum L.) grown under rain-fed condition at Zonal Research Station (BirsaAgricultural University), Chianki during rabi 2013-14. One hundred twenty seven selection indicesinvolving seed yield per plant and its six components were constructed using discriminant functiontechnique. In general, more the number of characters included in a selection index, the better wasits performance. The index based on six characters viz., seed yield per plant, biological yield perplant, harvest index, number of capsules per plant, number of seeds per capsule and 1000 seedweight, which had a genetic advance and relative efficiency of 59.9 g and 1196.20% followed by anindex based on five characters seed yield per plant, biological yield per plant, harvest index, numberof capsule per plant and number of seeds per capsule which possessed genetic gain and relativeefficiency of 59.9 g and 1185.12%, and for four characters viz., seed yield per plant, biological yieldper plant, harvest index and number of capsule per plant which consisted genetic gain and relativeefficiency 59.52 and 1147.29% respectively. The use of these indices is advocated for selecting highyielding genotypes of linseed.